Impact of dehydroepianrosterone (DHEA) supplementation on serum levels of insulin-like growth factor 1 (IGF-1): A dose-response meta-analysis of randomized controlled trials - Xie, Min; Zhong, Yanfa; Xue, Qing; Wu, Meirong; Deng, Xiaoxian; O. Santos, Heitor; Tan, Shing Cheng; Kord-Varkaneh, Hamed; Jiao, Peng (Experimental gerontology, 2020)
Inconsistencies exist with regard to the influence of dehydroepiandrosterone (DHEA) supplementation on insulin-like growth factor 1 (IGF-1) levels. The inconsistencies could be attributed to several factors, such as dosage, gender, and duration of intervention, among others. To address these inconsistencies, we conducted a systematic review and meta-analysis to combine findings from randomized controlled trials (RCTs) on this topic. Electronic databases (Scopus, PubMed/Medline, Web of Science, Embase and Google Scholar) were searched for relevant literature published up to February 2020. Twenty-four qualified trials were included in this meta-analysis. It was found that serum IGF-1 levels were significantly increased in the DHEA group compared to the control (weighted mean differences (WMD): 16.36 ng/ml, 95% CI: 8.99, 23.74; p = .000). Subgroup analysis revealed that a statistically significant increase in serum IGF-1 levels was found only in women (WMD: 23.30 ng/ml, 95% CI: 13.75, 32.87); in participants who supplemented 50 mg/d DHEA (WMD: 15.75 ng/ml, 95% CI: 7.61, 23.89); in participants undergoing DHEA intervention for >12 weeks (WMD: 17.2 ng/ml, 95% CI: 8.02, 26.22); in participants without an underlying comorbidity (WMD: 19.11 ng/ml, 95% CI: 10.69, 27.53); and in participants over the age of 60 years (WMD: 19.79 ng/ml, 95% CI: 9.86, 29.72). DHEA supplementation may increase serum IGF-I levels especially in women and older subjects. However, further studies are warranted before DHEA can be recommended for clinical use. •Supplementation with DHEA may increase serum IGF-I levels.•The effects occur especially in women and older subjects.•The findings cannot be endorsed as a substantial factor in clinical practice.